A Concept of Fusion Medicine - where Ayurveda Meets Allopathy - Parajuli, Bibek Raj; Koirala, Sanjib (Journal of Karnali Academy of Health Sciences, 2021)
There is a constant debate on the efficacy of medical treatments using Ayurveda versus allopathy. Staunch supporters of one method of treatment are quick to dismiss the other. The combination of ayurvedic and allopathic medicines has both advantages and disadvantages. Basic pharmacology of both ayurvedic and allopathic medicines should be included in both branches of medicine. Proper history should be taken before prescribing these drugs to avoid possible drug interactions among high risk patients. Positive aspects from both branches of medicine can be taken for the benefits of the patients.